The impact of transhumant livestock system on the diversity of two mountainous grasslands in Northern Greece - Karatassiou M.; Parissi Z.M.; Sklavou P.; Ispikoudis S. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The transhumant livestock system, which involves sheep and goats, is common in many countries of the Mediterranean basin. In Greece, transhumance uses the semi-natural vegetation of intermediate and high elevation grasslands for 5-6 months imposing variable pressures on the native vegetation. This paper investigated the impact of long term grazing of transhumant sheep and goats flocks on the diversity and land reclamation of two mountainous grasslands of Northern Greece. The experiment involved two high elevation Mediterranean grasslands of Northern Greece (Smolikas and Vermion mountains) located approximately 120 km apart. Measurements were carried out in the above areas in the middle of June 2012 including vegetation cover, while composition and the richness of the species were calculated. Thereafter, the index of similarity and plant species diversity and evenness were estimated. The results revealed no differences between the two grasslands regarding the (a) composition of species, (b) diversity of plant species, and (c) species richness. The percentage of vegetation cover was similar in the two grasslands, while the similarity index was small.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)